Loss of heterozygosity at 13q13 and 14q32 predicts BRCA2 inactivation in luminal breast carcinomas. Issue 12 (10th July 2013) - Pécuchet, Nicolas; Popova, Tatiana; Manié, Elodie; Lucchesi, Carlo; Battistella, Aude; Vincent‐Salomon, Anne; Caux‐Moncoutier, Virginie; Bollet, Marc; Sigal‐Zafrani, Brigitte; Sastre‐Garau, Xavier; Stoppa‐Lyonnet, Dominique; Stern, Marc‐Henri
<x xml:space="preserve">Abstract</x> BRCA2 is the major high‐penetrance predisposition gene for luminal (estrogen receptor [ER] positive) breast cancers. However, many BRCA2 mutant carriers lack family history of breast/ovarian cancers and do not benefit from genetic testing. Specific genomic features associated with BRCA2 inactivation in tumors could help identify patients for whom a genetic test for BRCA2 may be proposed. A series of ER‐positive invasive ductal carcinomas (IDCs) including 30 carriers of BRCA2 mutations and 215 control cases was studied by single‐nucleotide polymorphism (SNP) arrays. Cases and controls were stratified by grade and HER2 status. Independently, 7 BRCA2 and 51 control cases were used for validation. Absolute copy number and Loss of heterozygosity (LOH) profiles were obtained from SNP arrays by the genome alteration print (GAP) method. BRCA2 tumors were observed to display a discriminatively greater number of chromosomal breaks calculated after filtering out and smoothing <3 Mb variations. This argues for a BRCA2‐associated genomic instability responsible for long‐segment aberrations. Co‐occurrence of two genomic features—LOH of 13q13 and 14q32—was found to predict BRCA2 status with 90% of sensitivity and 87% of specificity in discovery series of high‐grade HER2‐negative IDCs and 100% of sensitivity and 88% of specificity in an independent series of 58 IDCs. Estimated positive predictive value was 17.2% (confidence interval: 6.7–33.5) in the whole series. In conclusion, the simplified BRCA2 classifier based on the co‐occurrence of LOH at 13q13 and 14q32 could provide an indication to test for BRCA2 mutation in patients with ER‐positive IDC.